Cost-effectiveness of Nutrition Policies to Discourage Processed Meat Consumption: Implications for Cancer Burden in the United States (OR16-01-19). (13th June 2019) - Kim, David; Wilde, Parke; Michaud, Dominique; Liu, Junxiu; Lizewski, Lauren; Onopa, Jennifer; Mozaffarian, Dariush; Zhang, Fang Fang; Wong, John
Abstract: Objectives: Processed meat is associated with increased risk of colorectal and stomach cancer, but health and economic impacts of policies to discourage processed meat consumption are not well-established. This paper aims to estimate cancer outcomes, costs, and cost-effectiveness of implementing two population-level policies on processed meat: 1) 10% excise tax and 2) mandatory warning label. Methods: We developed a probabilistic cohort-state transition model, including short-term and lifetime horizon, US healthcare and societal perspective, and 3% annual discount rates for costs and health outcomes. Our model simulated 32 subgroups by age, gender, and race/ethnicity from the US adult population and integrated nationally representative 2011–2014 data on processed meat consumption with etiologic effects of processed meat on cancer incidence, medical and indirect societal costs, and policy costs. Data sources for input parameters included NHANES, US Cancer Statistics, meta-analyses, and other published literature. Main outcomes were cancer incidence, quality-adjusted life-years (QALYs), policy and healthcare costs, productivity benefits, incremental cost-effectiveness ratios. Results: Over a lifetime, the 10% excise tax would prevent 77, 000 colorectal (95% uncertainty interval: 56, 800–114, 000) and 12, 400 stomach (6860–24, 700) cancer cases, add 591, 000 (418, 000–856, 000) QALYs, and generate net savings of 20.5B from healthcare and 23.4B from societal perspectives. The warning label policy would avert 84, 500 (56, 800–141, 000) and 14, 700 (6880–34, 500) colorectal and stomach cancer cases and add 648, 000 (416, 000–1080, 000) QALYs with net savings of 24.1B from healthcare and 27.3B from societal perspectives. In sensitivity analyses, greater health and economic benefits accrued to 1) younger populations, 2) subpopulations with greater cancer risk, and 3) those with higher baseline processed meat consumption. Conclusions: Our model shows that implementing an excise tax or warning label on processed meats would be a cost-saving strategy with substantial health and economic benefits. Our findings will encourage policymakers to consider nutrition-related policies to reduce cancer burden. Funding Sources: NIH/NIMHD. Supporting Tables, Images and/or Graphs: